Influence of Processing Parameters, Feedstock and Heat Treatment on the Microstructure of PBF-LB 316L Stainless Steel - Jacobsson, Petter (My University, 2026)
The increasing demand for reliable and rapidly deployable spare parts in highly regulated industries such as nuclear power has accelerated the interest in additive manufacturing (AM) of stainless steels. In this work, the influence of heat treatment, process parameters, powder type and part geometry on the microstructure of powder bed fusion-laser beam (PBF-LB) produced 316L stainless steel was investigated. Samples using both vacuum induction gas atomized (VIGA) and gas atomized (GA) were subjected to stress relieving (SR) and solution annealing (SA) and a combination of these treatments. Microstructural evolution was characterized primarily using light optical microscopy (LOM) and quantitative image analysis, with selected samples additionally characterized by EBSD. The results showed that stress relieving preserved the characteristic anisotropic melt pool and columnar grain structures formed during printing, while SA at 1200 ◦C promoted varying degrees of recrystallization depending on processing route and powder feedstock. Samples produced using GA powder exhibited extensive recrystallization and annealing twin formation after SA, whereas VIGA samples largely retained the original grain morphology despite identical HT schemes. Variations in laser power influenced melt pool geometry and porosity formation, but only limited effects on recrystallization behavior were observed. Part geometry showed minimal influence on recrystallization, although thin wall specimens were more susceptible to distortion during quenching. A custom image analysis method based on Frangi filtering was also developed to quantify grain morphology from etched LOM images. The findings demonstrate that recrystallization behavior in PBF-LB 316L SS is strongly dependent on the combined effects of feedstock condition, thermal history and processing route. This study highlights the complexity of grain boundary engineering in the anisotropic, non-equilibrium microstructure of additively manufactured stainless steels and contributes to the understanding of post-processing strategies for the tailoring microstructure of AM components intended to replace conventional 316L parts in nuclear power plants.